Entrepreneurial marketing in online businesses: the case of ethnic minority entrepreneurs in the UK. Issue 3 (13th June 2016) - Anwar, Muhammad Naveed; Daniel, Elizabeth
Abstract : Purpose: Many countries are seeing unprecedented levels of migration, raising questions about the economic contribution of individuals that settle in host countries. We explore the operation of online businesses by ethnic minority entrepreneurs. We apply an entrepreneurial marketing lens to explore how such entrepreneurs draw on the resources to market their businesses. We also consider if online businesses offer such entrepreneurs the opportunity to break out of the highly competitive sectors with which they are traditionally associated. Design/methodology/approach: Key informant interviews are undertaken with 22 entrepreneurs operating online businesses in the UK and augmented by complementary sources of data such as their web sites and press coverage. Findings: Use of an entrepreneurial marketing perspective demonstrates that marketing in such businesses is not haphazard or chaotic. Rather it reflects the emergent and flexible use of resources. The affordances of online businesses appear to offer opportunities for break out, but the reliance on incremental experimentation and copying others results in highly homogeneous approaches to marketing. We also provide empirical evidence of the link between visa status and entrepreneurial choices. Originality/value: Despite the popularity of online businesses, previous studies have not explored them as an opportunity for ethnic minority entrepreneurs. Our study moves the consideration of break out from market-entry to the ongoing marketing activities that sustain a business. It also demonstrates how the domains of ethnic minority entrepreneurship and entrepreneurial marketing can be brought together via a focus on resources. Finally, it enriches entrepreneurial marketing by evidencing connections with notions of effectuation and entrepreneur-venture fit.